Pituitary Stalk Interruption Syndrome: From Clinical Findings to Pathogenesis. (20th January 2017) - Wang, C.‐Z.; Guo, L.‐L.; Han, B.‐Y.; Su, X.; Guo, Q.‐H.; Mu, Y.‐M.
Abstract : Pituitary stalk interruption syndrome (PSIS) is a rare congenital defect manifesting with varying degrees of pituitary hormone deficiency. The signs and symptoms of PSIS during the neonatal period and infancy are often overlooked and therefore diagnosis is delayed. The typical manifestations of PSIS can be detected by magnetic resonance imaging. Several genes in the Wnt, Notch and Shh signalling pathways related to hypothalamic‐pituitary development, such as PIT1, PROP1, LHX3/LHX4, PROKR2, OTX2, TGIF and HESX1, have been found to be associated with PSIS. Nevertheless, the aetiology in the majority of cases still remains unknown. In the present review, we provide an overview of clinical features of PSIS and summarise our current understanding of the underlying pathogenic mechanisms for this rare syndrome. Furthermore, we propose future research directions that may help our understanding of the aetiology of PSIS.